A REVIEW OF NANOPARTICLE-BASED STRATEGIES FOR OVERCOMING THE BLOOD-BRAIN BARRIER IN NEURODEGENERATIVE DISEASE THERAPY - Thika Marliana; Bina Magar; Samuel Denis (Yayasan Adra Karima Hubbi, 2025)
Neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, and related disorders, remain difficult to treat effectively due to the restrictive nature of the blood–brain barrier, which severely limits drug delivery to the central nervous system. Many therapeutic agents with proven molecular efficacy fail to achieve clinical success because they cannot reach target sites in the brain at sufficient concentrations. This review aims to critically analyze nanoparticle-based strategies developed to overcome the blood–brain barrier and to evaluate their potential in neurodegenerative disease therapy. A narrative-integrative review method was employed, drawing on peer-reviewed articles indexed in major scientific databases, including studies on lipid-based, polymeric, inorganic, and biomimetic nanoparticles. The reviewed evidence indicates that nanoparticle systems significantly enhance brain delivery through mechanisms such as receptor-mediated transcytosis, adsorption-mediated transport, and biomimicry, leading to improved pharmacokinetics and therapeutic efficacy in preclinical models. Lipid-based and biomimetic nanoparticles demonstrate the greatest translational promise due to favorable safety and biological compatibility, while polymeric systems offer high design flexibility. Despite these advances, challenges related to long-term safety, reproducibility, and clinical translation persist. In conclusion, nanoparticle-based delivery represents a pivotal strategy for overcoming the blood–brain barrier, and continued interdisciplinary research is essential to translate these technologies into effective therapies for neurodegenerative diseases. Keywords: blood–brain barrier; nanoparticles; neurodegenerative diseases; nanomedicine; targeted drug delivery